The enhancement of mathematical problem solving ability and self-confidence of students through problem based learning - Ramadhani, Rahmi (Jurnal Riset Pendidikan Matematika, 2018)
This paper reported result of a research attempted to analyze: the increase in student’s MPS and SC using problem-based learning; and to look interaction between students’ PMK and learning to increase student’s MPS and SC. This type of research was a quasi-experimental. The population of this research was all students in SMA Negeri 6 Medan. Then 33 students were chosen as the experimental class and 33 students in other class was chosen as a control class by using purposive sampling technique. The data in this study were analyzed using Two Ways ANOVA. The result of validity of student’s MPS test is 0,808. Both reability of test was 0.86. The result of this research were: (1) The enhancement of student’s MPS ability and SC using problem-based learning was higher than conventional learning; (2) There is no interaction between student’s PMK and learning on student’s MPS ability and SC.